Meta Analysis on Nanoparticles: Structure, Properties, Prepration, Enviornmental Significance and Application - Rastogi, Vishakha; Verma, Navneet; Sharma, Vijay (Journal of Neonatal Surgery, 2025)
Nanoparticles have thousands of uses thanks to research activities over the last 20 years. Products with different features. They show different properties depending on their size. These properties make them reliable for many domestic and industrial based tasks, including chemical, pharma and biopharmaceutical applications , electrical researches and environmental based applications. Different types of heavy metal np such as lead, mercury, and tin have been found to be flexible usability and stable, do not degrade easily, and can cause many toxicities